Nucleolar proteins regulate stage‐specific gene expression and ribosomal RNA maturation in Trypanosoma brucei. Issue 4 (26th April 2013) - Schumann Burkard, Gabriela; Käser, Sandro; de Araújo, Patrícia Rosa; Schimanski, Bernd; Naguleswaran, Arunasalam; Knüsel, Sebastian; Heller, Manfred; Roditi, Isabel
Summary: Different life‐cycle stages of Trypanosoma brucei are characterized by stage‐specific glycoprotein coats. GPEET procyclin, the major surface protein of early procyclic (insect midgut) forms, is transcribed in the nucleolus by RNA polymerase I as part of a polycistronic precursor that is processed to monocistronic mRNAs. In culture, when differentiation to late procyclic forms is triggered by removal of glycerol, the precursor is still transcribed, but accumulation of GPEET mRNA is prevented by a glycerol‐responsive element in the 3′ UTR. A genome‐wide RNAi screen for persistent expression of GPEET in glycerol‐free medium identified a novel protein, NRG1 (N ucleolarR egulator ofG PEET 1), as a negative regulator. NRG1 associates with GPEET mRNA and with several nucleolar proteins. These include two PUF proteins, TbPUF7 and TbPUF10, and BOP1, a protein required for rRNA processing in other organisms. RNAi against each of these components prolonged or even increased GPEET expression in the absence of glycerol as well as causing a significant reduction in 5.8S rRNA and its immediate precursor. These results indicate that components of a complex used for rRNA maturation can have an additional role in regulating mRNAs that originate in the nucleolus.